STRATEGI PEMASARAN DENGAN MENGGUNAKAN METODE SWOT DI UKM XYZ - Muhammad Nur (Research Center University of Pahlawan Tuanku Tambusai, 2021)
UKM XYZ is an industry engaged in the food sector. The problems that occur in UKM XYZ are the promotion strategy implemented is not enough to increase sales, there are competitors with similar businesses. From the problems that occur have an impact on sales and decreased revenue. The purpose of this research is to identify internal and external factors that influence and form elements of marketing strategy, analyze strengths and weaknesses as well as opportunities and threats to see the current position.. The method used in this research is the SWOT method. The SWOT method is a method used to determine the strategy to be pursued based on the strengths and weaknesses as well as the opportunities and threats that exist in UKM XYZ. Through analysis of the strengths and weaknesses as well as opportunities and threats to UKM XYZ with the calculation of EFE and IFE matrices, the results of the current position of UKM are in quadrant II, where the right strategy to be implemented is the strategy of growth and development.